Meritocracy: a post-war conceptual history - Civil, David (2020)
By using the tools of conceptual history and ideology studies, this thesis traces the changing meaning of meritocracy in post-war Britain. In doing so it uses the concept as a lens through which to explore broader questions of intellectual politics, from the rise of the ‘affluent society’ to the onset of national ‘decline’. Meritocracy traversed the political spectrum: for social democrats it was a suitable ‘stop-gap’ that would lead to gradually greater equality in the future; for conservatives it was a satisfactory end state which preserved a democratically legitimate social elite. Over the course of the late 1950s and the 1960s, however, the concept became overburdened with ideological baggage. In the late 1960s, faced with student protests, the rise of a nascent identity politics highlighting the implicit biases of the meritocratic social order, as well as burgeoning sociological evidence that the principles of meritocracy had failed to deliver greater equality, classlessness, economic growth or redistribution, the concept fragmented. The collapse of the meritocratic moment not only threatened the survival of the concept but also those ideological formations, namely Revisionist Social Democracy and Middle Way Conservatism, which had elevated meritocracy to privileged positions in their respective morphologies. While these ideologies struggled to formulate alternative distributive principles, new ideological constellations emerged which privileged different criteria. The most significant of these was the market. The market proposed solutions to the central tensions and conceptual problems which emerged out of meritocracy’s demise in the late 1960s. This thesis therefore tells a story about the way market principles displaced those that were ascendant during Britain’s ‘meritocratic moment’.